2017
DOI: 10.5994/jei.5.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Keefektifan Telenomus remus (Nixon) (Hymenoptera: Scelionidae) dalam mengendalikan hama tanaman bawang daun Spodoptera exigua Hübner (Lepidoptera: Noctuidae)

Abstract: The objective of this research is to study the effectiveness of T. remus as biocontrol agent for S. exigua. The study was conducted by releasing a set of T. remus females on potted onion plants that have been attacked by S. exigua. Three different parasitism level was artificially created by releasing different numbers of females: low rate parasitism (release of 4 adult females), moderate parasitism (7 females) and high parasitism level (11 females). The result of this study showed that T. remus is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The parasitoid antennae of T. remus exhibit sexual dimorphism. Male antennae have 12 segments, whereas female antennae have 11 parts, including four mace segments [24].…”
Section: Resultsmentioning
confidence: 99%
“…The parasitoid antennae of T. remus exhibit sexual dimorphism. Male antennae have 12 segments, whereas female antennae have 11 parts, including four mace segments [24].…”
Section: Resultsmentioning
confidence: 99%
“…Liao et al (2019) reported 60.19% field parasitism rate of S. frugiperda by T. remus.. So far, T. remus has been reported to be used as a biological control agent of S. litura (Susiawan & Yuliarti, 2017) and S. exigua (Buchori et al, 2017), another armyworm pest species that have long been existed in Indonesia (Kalshoven, 1981). In this study, we compare the performance of T. remus in parasiting S. frugiperda and S. litura under laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Telenomus remus is an egg parasitoid of various lepidopteran pest species including genus Spodoptera (CABI, 2019b). Buchori, Herawati, and Sari (2017) reported that the release of T. remus able to suppress 48% population of S. exigua in potted onion plants. Meanwhile, Satyanarayana, Ballal, and Rao (2005) reported 96% parasitism rate of S. litura eggs by T. remus.…”
mentioning
confidence: 99%
“…[8,15]. Telenomus and Trichogramma are egg parasitoids that have the potential to become natural enemies of many important pests [16], such as Scirpophaga innotata [17], Helicoverpa armigera [18], Ostrinia furnacalis [19], and S. exigua [20]. Sari et al [12,13] has researched T. remus's potential as S. frugiperda's egg parasitoid.…”
Section: Discussionmentioning
confidence: 99%